Propagation of Chickpea in vitro (Baghdad Science Journal, 2025)
Apical meristems, lateral buds, anthers of immature flowers and immature embryos of chickpea ( Cicer arietinum L.) were cultured on MS media with different growth regulators and incubated for 6 weeks at 25-27?C with 16 hrs photoperiod for callus initiation. Results indicated that 1 and 0.1 mg/l of 2,4-D and BA were suitable for callus initiation when apical meristems and lateral buds were used. While 2 and 0.5 mg/l of both growth regulators were essential for immature embryos. It was noticed that using chickpea anthers of the MS medium must contain 1mg/l 2ip and 0.5 mg/l IAA. However, MS medium supplemented with 1-3 mg/l of BA and 2,4-D respectively was good for callus initiation from lateral buds, anther and immature embryos. However, callus differentiations in chickpea were successfully obtained when 2-3 mg/l of IAA, 2-2.5mg/l of kinetin or 0.1 mg/l of NAA and 2 mg/l of kinetin were used. Data of regeneration and culture maintenance revealed that half strength of MS medium supplemented with 2, 2.5 mg/l of IAA and kinetin respectively or 0.005mg/l and 0.05 mg/l of NAA and BA respectively was the best. The importance of this method in propagation were used for improving and screening resistant chickpea germplasm aginst Fusarium wilt disease.